The Implementation of the Time Token Learning Model Assisted by Picture Series to Improve the Speaking Skills of Fifth-Grade Elementary School Students - Muhammad Asrul Sultan; Nur Ilmi; Dwi Asfika Iskandar (PT. Lontara Digitech Indonesia, 2026)
The problem faced in Indonesian language learning, particularly in speaking skills, is the low ability of students to express opinions, where only a few students are active while most others remain passive. This study aims to determine the implementation of the Time Token learning model assisted by picture series on the Indonesian speaking skills of fifth-grade students at UPT SD Negeri 99 Pekajo. This study is classroom action research (CAR) conducted in three cycles, with the stages of planning, implementation, observation, and reflection in each cycle. The research subjects were one teacher and 13 students. Data collection techniques were carried out through observation, documentation, and speaking skills tests. The results of the study showed an improvement in students’ speaking skills from cycle to cycle, namely from poor qualification in Cycle I, increasing to fair qualification in Cycle II, and reaching good qualification in Cycle III. Thus, the implementation of the Time Token learning model assisted by picture series was proven effective in improving students’ speaking skills.